Utilization of whole sorghum crop residues for bioethanol production. Issue 2 (15th April 2016) - Nasidi, Muhammad; Agu, Reginald; Deeni, Yusuf; Walker, Graeme
Abstract : Sorghum is the fifth most important cereal worldwide and is a major source of agricultural residues in tropical regions. Bioconversion of whole sorghum crop residues comprising stalks, leaves, peduncles and panicles to ethanol has great potential for improving ethanol yield per sorghum crop cultivated, and for sustainable biofuel production. Effective pretreatment of sorghum lignocellulosic biomass is central to the efficiency of subsequent fermentation to ethanol. Previous studies have focused on the bioconversion of sorghum stalks and/or leaves only to bioethanol, but the current study is the first report dealing with whole crop residues. We specifically focused on the impact of Nigerian sorghum cultivation location and cultivar type on the potential ethanol yield from whole sorghum crop residues. Efficient bioconversion of whole sorghum residues to ethanol provides a sustainable route for utilization of crop residues thereby providing a non‐food feedstock for industrial‐scale bioethanol production. Copyright © 2016 The Institute of Brewing & Distilling